Determinan Kesempatan Kerja di Indonesia Tahun 1991-2022 - Setianto, Chika Aisyah Putri; Mandai, Syafri (Peneliti.net, 2025)
The number of workers continues to grow in Indonesia, this could be a good thing if it is balanced with increasing job opportunities for workers. Several factors that can increase job opportunities in Indonesia are economic growth, education level, and minimum wages. time series data is utilised in this research from 1991 to 2022. The method used is quantitative with the ECM analysis model. The research results show that economic growth, both in the long and short term, has a positive and significant effect on employment opportunities. Average years of schooling as a proxy for education negatively and significantly affects job opportunities. Meanwhile, minimum wages do not affect employment opportunities in either the long or short term.